The role of the housing market in workers' resilience to job displacement after firm bankruptcy - J. Meekes; Wolter H.J. Hassink (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2016)
This paper examines the importance of the housing market for workers who have become displaced. We used Dutch administrative data, which were analysed with a quasi-experimental empirical design. The estimates indicate that displaced workers experience an increase in commute and decrease in moving home, employment and wage. Furthermore, these patterns change across time – the evidence suggests that workers who have longer unemployment duration prefer lower gains in commute to higher losses in wage. Finally, the worker-specific housing state has a substantial effect on the costs of job displacement, which is comparable to the effects of various demographic and job characteristics.
Keywords: 330; Housing; Unemployment; Wages; Commuting; Mobility; Worker Characteristics